Remoción de poste de fibra del canal radicular previo al retratamiento endodontico. - Flores Napa, Edwin David (2025)
Removing fiberglass posts presents risks to the remaining dental structure, potentially altering root canal morphology and inducing undue stress. The visual similarity between the post and dentin necessitates specialized techniques and instruments like burs and ultrasonic tips for extraction, aiming to preserve the remaining tooth structure. Computed tomography aids in determining the root canals' three-dimensional orientation, optimizing removal. This study aimed to evaluate fiberglass post-extraction techniques, compare clinical and biomechanical factors justifying their removal, and explore post-retreatment prosthetic alternatives. The researcher conducted a descriptive literature review using the PICO methodology and PRISMA guidelines. Selecting fifteen relevant articles from updated scientific databases based on inclusion/exclusion criteria, keywords, and search strategies was vital. The analysis focused on various removal techniques, clinical and biomechanical factor comparisons, and post-retreatment prosthetic options. Results indicate that specialized tools like the "Fiber Post Removal Kit," irrigating solutions such as EDTA, and magnification devices are crucial during fiberglass post removal. Biomechanics significantly influences the procedure, as improper force distribution can lead to fractures. Reconstruction options include full crowns, resin-cemented fiberglass posts, fixed bridges, implants, and CAD/CAM restorations. Ultimately, assessing periodontal health and masticatory function is vital for procedural success.